PENDIDIKAN BAGI PENDATANG DI TENGAH MAYORITAS MASYARAKAT PRIBUMI - Iwan Hermawan (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2014)
This article is concerned with the conception of education for immigrants in the middle of the indigenous majority. As it is known that the movement of people from one place to another is a common and this effect on people’s lives, both migrants and natives. These conditions further reinforce the diversity of Indon esian society and encourage the need for multicultural education. Feature of the present time that every student h as the same rights in acquiring cultural knowledge and educational process is to be developed to further highlig ht the cultural diversity that supports the idea of mutual respect for differences among people. Meanwhile, the introduction of the values of the dominant culture of the local community needs to be done as the basis for a process of interaction and adaptation processes in a common life in the community.